Impedance e-tongue instrument for rapid liquid assessment - Cabral, Flavio P. A.; Bergamo, Bruno B. [UNESP]; Dantas, Cleber A. R. [UNESP]; Riul, A.; Giacometti, Jose A. [UNESP] (American Institute of Physics (AIP), 2009)
We present a compact and easy to handle instrument developed to perform rapid analysis of liquids utilizing an electronic tongue system. Briefly, the e-tongue used here is based on impedance measurements of an array of sensing units fabricated with ultrathin films of different materials deposited onto gold interdigitated electrodes. The instrument has the capability of measuring up to eight different sensor sets, each comprising an array of eight sensing units, and can perform a series of measurements in less than half of an hour. Additionally, there is a user-friendly software interface for instrument control, allowing the statistical correlation of samples using principal component analysis.
Keywords: electric impedance measurement; electronic tongues; gold; principal component analysis